Use of lifestyle interventions in primary care for individuals with newly diagnosed hypertension, hyperlipidaemia or obesity: a retrospective cohort study - Julia M Lemp; Meghana Prasad Nuthanapati; Till W Ba¨rnighausen; Sebastian Vollmer; Pascal Geldsetzer; Anant Jani (My University, 2022)
Objective: Lifestyle interventions can be efficacious in reducing cardiovascular disease risk factors and are recommended as first-line interventions in England. However, recent information on the use of these interventions in primary care is lacking. We investigated for how many patients with newly diagnosed hypertension, hyperlipidaemia or obesity, lifestyle interventions were recorded in their primary care electronic health record. Design: A retrospective cohort study. Setting: English primary care, using UK Clinical Practice Research Datalink. Participants: A total of 770,711 patients who were aged 18 years or older and received a new diagnosis of hypertension, hyperlipidaemia or obesity between 2010 and 2019. Main outcome measures: Record of lifestyle intervention and/or medication in 12 months before to 12 months after initial diagnosis (2-year timeframe). Results: Analyses show varying results across conditions: While 55.6% (95% CI 54.9–56.4) of individuals with an initial diagnosis of hypertension were recorded as having lifestyle support (lifestyle intervention or signposting) within the 2-year timeframe, this number was reduced to 45.2% (95% CI 43.8–46.6) for hyperlipidaemia and 52.6% (95% CI 51.1–54.1) for obesity. For substantial proportions of individuals neither lifestyle support nor medication (hypertension: 12.2%, 95% CI 11.9–12.5; hyperlipidaemia: 32.2%, 95% CI 31.2–33.3; obesity: 43.9%, 95% CI 42.3–45.4) were recorded. Sensitivity analyses confirm that limited proportions of patients had lifestyle support recorded in their electronic health record before they were first prescribed medication (diagnosed and undiagnosed), ranging from 12.1% for hypertension to 19.7% for hyperlipidaemia, and 19.5% for obesity (23.4% if restricted to Orlistat). Conclusions: Limited evidence of lifestyle support for individuals with cardiovascular risk factors (hypertension, hyperlipidaemia, obesity) recommended by national guidelines in England may stem from poor recording in electronic health records but may also represent missed opportunities. Given the link between progression to cardiovascular disease and modifiable lifestyle factors, early support for patients to manage their conditions through non-pharmaceutical interventions by establishing lifestyle modification as first-line treatment is crucial.
Keywords: Disease prevention, cardiovascular disease, primary care, lifestyle intervention